Detection of Tannerella forsythia from saliva samples in different ethnic majority groups in Sarawak - Elexson, Nillian; Grace, Bebey; Fatin Nabilah, Ngu; Nur Diyana, -; Amirah Zakirah, -; Eddy, Boli; Chung, Malvin Hsien Liang (Malaysian Society for Molecular Biology and Biotechnology, 2021)
Nowadays racial and ethnic differences in health care has become a growing concern. It is one of the critical determinant in influencing the genotype of the host in which may results in some diseases such as periodontal disease. Tannerella forsythia can be found in oral cavity and have the strongest relation in resulting on the destruction of connective tissue in periodontal disease. This research is aim to investigate the prevalence of periodontal pathogens, particularly T. forsythia in four major ethnic groups in Sarawak which may result in periodontal disease in Sarawak. This disease may due to the results from the infection of the tissue supporting the teeth. A total of (n = 40) saliva samples consist of 10 samples for each ethnic groups such as Iban, Malay, Chinese and Bidayuh were collected in Kuching and Kota Samarahan using culture-independent method. The DNA was extracted from saliva based on Phenol Chloroform Isoamyl Alcohol method. After that, 16S rRNA gene was then amplified via PCR for bacterial detection using 27 F and 1492 R primers, followed by PG-F and PG-R primers set in identifying T. forsythia. The PCR product was observed on 1.5% gel electrophoresis. As a result, the presence of bacteria T. forsythia was found more frequently from saliva samples of ethnic in Iban (70%), followed by Malay (60%), Bidayuh (60%) and lastly Chinese (50%). The differences of demographic, certain cultural beliefs and practices might affect the oral health status. This finding show that it may help to identify the risk groups and has contributed an additional evidence for the association between ethnicity and periodontal disease.